2020
DOI: 10.4330/wjc.v12.i7.351
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic muscle mass assessment in patients after cardiac surgery

Abstract: BACKGROUND Patients undergoing cardiac surgery particularly those with comorbidities and frailty, experience frequently higher rates of post-operative morbidity, mortality and prolonged hospital length of stay. Muscle mass wasting seems to play important role in prolonged mechanical ventilation (MV) and consequently in intensive care unit (ICU) and hospital stay. AIM To investigate the clinical value of skeletal muscle mass assessed by ultrasound early after cardiac sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 34 publications
0
13
0
14
Order By: Relevance
“…Twenty studies took serial measurements of the same muscle group to describe longitudinal changes in muscle mass. All 20 of these longitudinal studies found statistically significant changes in muscle measurements over time, which ranged from 15% to 30% reduction in muscle measurement between Day 0 (baseline) and Day 20 24,25,28,30,32,33,35–39,41,42,44,45,47,49,56–58 …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Twenty studies took serial measurements of the same muscle group to describe longitudinal changes in muscle mass. All 20 of these longitudinal studies found statistically significant changes in muscle measurements over time, which ranged from 15% to 30% reduction in muscle measurement between Day 0 (baseline) and Day 20 24,25,28,30,32,33,35–39,41,42,44,45,47,49,56–58 …”
Section: Resultsmentioning
confidence: 96%
“…The number of publications over the last 18 months ( n = 18 studies) was similar to that of the preceding 11 years ( n = 19 studies) highlighting the recent surge of new evidence ( Figure 2 ). Data from 26 prospective observational studies 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 (of which 6 were cohort studies, 44 , 45 , 46 , 47 , 48 , 49 7 cross‐sectional studies, 27 , 50 , 51 , 52 , 53 , 54 , 55 3 randomized control trials, 56 , 57 , 58 and 1 post hoc analysis of a negative trial) were included. 59 Five of the 37 studies involved an interventional arm [critical care nutritional intervention ( n = 4) 44 , 56 , 57 , 58 and an exercise intervention in breast cancer ( n = 1) 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In another recent study, we have shown that skeletal quadriceps muscle mass presented with a trend to a decrease in patients after cardiac surgery post-ICU admission and was associated with prolonged duration of MV and ICU length of stay. 23 Neuromuscular electrical stimulation (NMES) as an alternative form of exercise seems beneficial for preserving muscle mass and strength, 24,25 local and systemic microcirculation 26,27 in critically ill patients and also might reduce the duration of mechanical ventilation and ICU stay. 25,28 NMES has the advantage that can be applied even in sedated patients, an action that might enhance early mobilization, particularly in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…The perils of immobility during hospitalisation have been well described in the literature, and immobility has been associated with muscle weakness (Dimopoulos et al, 2020), reduced bone mineral density (Parry & Puthucheary, 2015), increased incidence of pressure ulcers, deconditioning, increased injuries from falls and increased length of hospital stay (Miller et al, 2016;Peiris et al, 2013).…”
Section: Introductionmentioning
confidence: 99%